2011
DOI: 10.1088/1748-9326/6/4/049504
|View full text |Cite
|
Sign up to set email alerts
|

The greenhouse impact of unconventional gas for electricity generation

Abstract: In our discussion of the use of global warming potential (GWP) values in the Howarth et al (2011) paper, our text implies that the GISS group's 2009 and 2010 papers (Shindell et al 2009 andUnger et al 2010) were contradictory. Such an interpretation does not reflect the conclusions of those papers and was not our intention. First, the 2009 and 2010 papers address GWP and radiative forcing, respectively. Our intentions in that paragraph were (a) to illustrate the possible ways that the GWP and radiative forcing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
84
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 5 publications
0
84
0
2
Order By: Relevance
“…They concluded that relatively straightforward measures could be implemented to minimize the potential release of greenhouse gases associated with the extraction of gas from shale (26). A more recent study by Hultman, et al (27) adopting a transparent and consistent approach to comparing the GHG footprints of conventional natural gas, shale gas, and coal, concluded that in terms of electricity generation the GHG impacts of shale gas are 11% higher than those for conventional gas (higher than the value reported by Jiang et al), but only 56% of the impact expected for coal.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that relatively straightforward measures could be implemented to minimize the potential release of greenhouse gases associated with the extraction of gas from shale (26). A more recent study by Hultman, et al (27) adopting a transparent and consistent approach to comparing the GHG footprints of conventional natural gas, shale gas, and coal, concluded that in terms of electricity generation the GHG impacts of shale gas are 11% higher than those for conventional gas (higher than the value reported by Jiang et al), but only 56% of the impact expected for coal.…”
Section: Discussionmentioning
confidence: 99%
“…Published averaged fugitive methane emissions emitted as a percent of total natural gas production 13,27,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] . Please click here to view a larger version of this figure.…”
Section: Figure 1 Fugitive Methane Emissionsmentioning
confidence: 99%
“…The climate implications of such abundant natural gas have been hotly debated. Some researchers have observed that abundant natural gas substituting for coal could reduce carbon dioxide (CO 2 ) emissions [3][4][5][6] . Others have reported that the non-CO 2 greenhouse gas emissions associated with shale gas production make its lifecycle emissions higher than those of coal 7,8 .…”
mentioning
confidence: 99%
“…2 Potsdam Institute for Climate Impact Research, PO Box 60 12 03, D-14412 Potsdam, Germany. 3 BAEconomics, PO Box 5447, Kingston, Australian Capital Territory 2604, Australia. 4 Resources for the Future, 1616 P Street Northwest, Washington, DC 20036, USA.…”
mentioning
confidence: 99%